Produção de sulfato de potássio a partir de cloreto de potássio e sulfato de amônio : estudos de equilíbrio sólido-líquido e desenvolvimento de processo - Viola, Dimas Henrique Lanfredi (Universidade Federal de São Carlos, 2016)
Potassium is one of the basic nutrients for plants and their concentration in the soil is insufficient to produce high quality crops, so it should be an essential component in the composition of fertilizers. Fertilizers containing potassium chloride provide chloride ions in large quantities in the soil, but many plants are sensitive to chloride ion, for example, crops (potatoes, tomatoes, red pepper, citrus and tobacco). To these cultures recommends the use of fertilizers containing potassium sulfate instead of fertilizers containing potassium chloride, being less harmful. Potassium sulfate (K2SO4) also provides the sulfate ion ( 2 4 SO ), which contains elemental sulfur, essential for the growth of plants. This information motivated research present in this thesis on the development of a potassium sulfate production process which facilitates production in Brazil in order to reduce or eliminate dependency on the importation, to obtain a high purity product and develop a viable environmental process and economically. Potassium sulfate was proposed to be produced through chemical reaction reaction (NH4)2SO4 + 2 KCl → K2SO4 + 2 NH4Cl in aqueous-alcoholic medium at ambient conditions using ethanol as antisolvent. The presence of ethanol decreases the solubility of the potassium sulfate. For the development of the process, the equilibrium solid-liquid phases (ESL) binary systems (water-potassium chloride and water-ammonium sulfate), the ternary system (water-potassium chloride-ammonium sulfate) and quaternary system (waterpotassium chloride-ammonium sulfate-ethanol) was studied and thermodynamic models were used for adequacy finding regarding the prediction of ESL. The thermodynamic models used for the binary systems were: Güntelberg equation, Davies equation, Debye-Hückel extended law, Bromley model, Meissner model, Pitzer model (ASPEN PLUS®) e electrolyte NRTL model (ASPEN PLUS®). For the ternary system, evaluated the Güntelberg equation, Davies equation, Debye-Hückel extended law, Bromley multicomponent model, Meissner multicomponent model, Pitzer model (ASPEN PLUS®) and electrolyte NRTL model (ASPEN PLUS®). Finally, thermodynamic models used for the quaternary system are electrolyte NRTL model (ASPEN PLUS®) and UNIQUAC-Debye-Hückel model. The developed process proved to be economically unfeasible, despite a positive gross profit because the gross profit is lower than the production costs. Costs for recovery of ethanol by distillation make impossible the process, generating negative values for the economic parameters, payback period and net present value.
Keywords: Equilíbrio sólido-líquido; Cristalização; Sulfato de potássio; Desenvolvimento de processo; Análise econômica; Solid-Liquid equilibrium; Crystallization; Potassium sulfate; Process development; Economic analysis; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA